ANALISIS PENGARUH PEMBERITAAN NEGATIF PERBANKAN SYARIAH DAN REGULASI KEUANGAN SYARIAH TERHADAP MINAT MENABUNG DI BPRS AMANAH UMMAH LEUWILIANG BOGOR - Muttaqin, Rizal; Trihantana, Rully; Anwar, Miftakhul (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This research aims to analyze the influence of negative news coverage of Islamic banking and Islamic financial regulations on the savings interest in Islamic banks (a study of customers at the head office of BPRS Amanah Ummah Leuwiliang). The research method used was quantitative descriptive, involving a research sample of 261 savings customers at the head office of PT BPRS Amanah Ummah. The research findings indicate that there is an influence of negative news coverage on the savings interest, which was obtained through a negative regression equation, meaning that there is a negative influence of news coverage on the savings interest. The research results also show that there is an influence of Islamic financial regulations on the savings interest, which was obtained through a positive regression equation, meaning that there is a positive influence of Islamic financial regulations on the savings interest. Therefore, it can be concluded that there is a partial influence of negative news coverage and Islamic financial regulations on the savings interest.